A Global Count of the Extreme Poor in 2012 : Data Issues, Methodology and Initial Results - Ferreira, Francisco H. G.; Chen, Shaohua; Dabalen, Andrew; Dikhanov, Yuri; Hamadeh, Nada; Jolliffe, Dean; Narayan, Ambar; Prydz, Espen Beer; Revenga, Ana; Sangraula, Prem; Serajuddin, Umar; Yoshida, Nobuo (World Bank, Washington, DC, 2015)
The 2014 release of a new set of purchasing power parity conversion factors (PPPs) for 2011 has prompted a revision of the international poverty line. In order to preserve the integrity of the goalposts for international targets such as the Sustainable Development Goals and the World Bank’s twin goals, the new poverty line was chosen so as to preserve the definition and real purchasing power of the earlier $1.25 line (in 2005 PPPs) in poor countries. Using the new 2011 PPPs, the new line equals $1.90 per person per day. The higher value of the line in US dollars reflects the fact that the new PPPs yield a relatively lower purchasing power of that currency vis-à-vis those of most poor countries. Because the line was designed to preserve real purchasing power in poor countries, the revisions lead to relatively small changes in global poverty incidence: from 14.5 percent in the old method to 14.1 percent in the new method for 2011. In 2012, the new reference year for the global count, we find 12.7 percent of the world’s population, or 897 million people, are living in extreme poverty. There are changes in the regional composition of poverty, but they are also relatively small. This paper documents the detailed methodological decisions taken in the process of updating both the poverty line and the consumption and income distributions at the country level, including issues of inter-temporal and spatial price adjustments. It also describes various caveats, limitations, perils and pitfalls of the approach taken.